CONSTRUCTING ESP-BASED ENTREPRENEURSHIP CURRICULUM FOR TEACHER TRAINEES: A NEED ANALYSIS OF BUILDING CREATIVE LIFE SKILLS - Lilies Youlia Friatin; Jamilah Jamilah (JALL (Journal of Applied Linguistics and Literacy), 2022)
Today, entrepreneurship education is a crucial component of the Indonesian government's efforts to reduce the number of unemployment. Higher Education students are expected to show entrepreneurial skills as preparation for their future life as the nation's future leaders in 21 century. Global entrepreneurship competition encourages students to master English in order to become skilled entrepreneurs on both a national and international scale. Higher education gives big role in preparing human resources. Lesson plan as part of curriculum, should be designed in accordance with the students need of particular skill. The existing lesson plan as teacher guide is important to examine. Hence, the research question of this research is, “How does the existing lesson plan of ESP (English for Entrepreneurship) represent entrepreneur skill of learners? This research uses a qualitative approach, document analysis. The research instrument used is the English lesson plan of ESP (English for Entrepreneurship). The results showed that lesson plan of ESP (English for Entrepreneurship) represent entrepreneur skill of learners. It can be seen on course objective; a) Students understand the nature of entrepreneurship, b) Students are able to build relationship in business, c), Students are able to develop their interpersonal skills in entrepreneur, d) Students can communicate effectively as an entrepreneur, e) Students understand how to negotiate and win the negotiation in business, f) Students are able to speak in front of public to achieve the business goals. It’s relevant with the basic need of entrepreneurs’ skill.